Peran Dompet Digital dalam Meningkatkan Kualitas Keuangan UMKM Menuju Era Society 5.0 - Wahid; Agit, Alamsyah; Ramadhani, Salsabila Eka (Forum Kerjasama Pendidikan Tinggi, 2023)
The use of financial applications in modern times can be found in various activities, including economic activities, the era of society 5.0 is marked by the emergence of technology that can assist various human activities, but this concept requires humans to be able to live side by side with this technology. Thus, it is necessary to maximize the use of technology in business activities. One form of business that contributes greatly to economic activity in general is MSMEs, but the lack of application of technology in MSMEs is a challenge and a threat that can become a factor inhibiting MSME growth in the future. This activity aims to add insight and assist MSMEs in implementing the use of digital financial applications such as digital wallets to support performance and strengthen competitiveness. This activity was carried out in the Mattoanging Village, Makassar City, with 38 participants who were MSME owners, a series of events carried out in three stages, namely the preparation stage, the implementation stage which consisted of delivering material, question and answer sessions, and discussion sessions, as well as the evaluation stage, to identify the shortcomings of this activity as a reference for future development. The results of this activity show the enthusiasm of MSME owners to immediately implement the use of digital financial applications, but there are some MSME owners who still prefer to use conventional transaction methods or in cash.